Metabolomics Profiling Reveals Critical Roles of Indoxyl Sulfate in the Regulation of Innate Monocytes in COVID-19 - Liqing He; Yunke Wang; Fang Yuan; Samantha Morrissey; Anne E. Geller; Xiaoling Hu; Raobo Xu; Xipeng Ma; Huang-ge Zhang; Kenneth McLeish; Jiapeng Huang; Xiang Zhang; et al. (Cells)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is intricately related to the reprogramming of host metabolism. However, existing studies have mainly focused on peripheral blood samples and barely identified specific metabolites that are critically involved in the pathology of coronavirus disease 2019 (COVID-19). In the current small-scale study, we performed metabolic profiling in plasma (n = 61) and paired bronchoalveolar lavage fluid (BALF) samples (n = 20) using parallel two-dimensional liquid chromatography–mass spectrometry (2DLC-MS). In addition, we studied how an identified metabolite regulates the immunopathogenesis of COVID-19. The results unveiled distinct metabolome changes between healthy donors, and moderate and severe patients in both plasma and BALF, indicating that locations and disease severity play critical roles in COVID-19 metabolic alteration. Notably, a vital metabolite, indoxyl sulfate, was found to be elevated in both the plasma and BALF of severe COVID-19 patients. Indoxyl sulfate selectively induced TNF-α production, reduced co-stimulatory signals, and enhanced apoptosis in human monocytes. Moreover, its levels negatively correlated with the strength of co-stimulatory signals and antigen presentation capability in monocytes of COVID-19 patients. Collectively, our findings suggest that the levels of indoxyl sulfate could potentially serve as a functional biomarker to monitor COVID-19 disease progression and guide more individualized treatment for COVID-19 patients.